Clinical performance of two different CAD/CAM-fabricated ceramic crowns: 2-Year results - Seydler, Bodo; Schmitter, Marc (The journal of prosthetic dentistry, 2015)
Statement of problem - Recently, technical problems, especially chipping, have been reported for ceramic restorations; as a result, ceramic crowns produced entirely by computer-aided design and computer-aided manufacture (CAD/CAM) have become popular because the incidence of chipping is less. - Purpose - The purpose of this study was to report on 2-year results for 2 different types of CAD/CAM ceramic crowns placed in adult patients in a dental practice. - Material and methods - Sixty participants who required a crown for a first or second molar were randomly assigned to 1 of 2 groups. Crowns in the veneered zirconia (VZ) group were made of zirconia frameworks veneered with CAD/CAM-produced lithium disilicate ceramic; the other group’s crowns were made of monolithic lithium disilicate (MLD) ceramic. Each crown was reviewed after 2 weeks, 1 year, and 2 years by using modified the US Public Health Service (USPHS) criteria. Statistical analysis was performed by using the log-rank test, nonparametric tests, and Kaplan-Meier survival analysis. - Results - All 60 participants were recalled after 1 and 2 years. In the VZ group, 2 endodontic complications occurred, and deterioration of periodontal health was observed for 3 participants. In the MLD group, 2 endodontic complications occurred within 2 years. In both of the groups, no caries or marginal discoloration was observed. No technical complications, for example, cracks, chipping, or fractures, were detected after 2 years. The shape and appearance of all crowns were assessed positively by the examining dentist. The log-rank test showed no significant differences in respect to technical or biologic complications (P=.324). - Conclusion - For both types of single-crown restoration, no technical failures occurred. The number of biological complications did not differ significantly between the types of crowns.
Gesehen am 16.06.2020